Structural modal study of vertical system vibration based on large axial Cross-Wedge rolling mill - Ma, Chuanchuan; Zhao, Xinglong; Zhong, Wenchang; Wang, Junjie; Xu, Junsheng; Zhang, Yang; Chu, Zhibing (Sound & Vibration, 2026)
With the surge in demand for large shaft components in the railway transportation industry, traditional rolling mills are insufficient to meet actual production needs, leading to the development of wedge cross-rolling mill equipment suitable for producing large shaft components. This paper focuses on the study of the vibration characteristics of the vertical system of large axial Cross-Wedge rolling mill. By constructing a four-degree-of-freedom (4-DoF) vertical vibration dynamic model of the mill frame structure, the vibration characteristics of the vertical system were investigated, and the natural frequencies and main vibration modes of each order were obtained. To facilitate subsequent research and optimization of the overall mill structure, the 4DoF vertical system model was simplified into a symmetric single-degree-of-freedom (SDoF) model, and the sensitivity of the second-order mode to stiffness was explored. At the same time, finite element analysis (FEM) was used to conduct modal analysis on the mill vertical system, and vertical system velocity signals were obtained through on-site data collection. The results indicate that the simplified vertical system structural model matches the vibration characteristics of the mill's vertical system, and the natural frequencies of the vertical system calculated are basically consistent with the results from modal analysis and on-site data collection. This study provides a theoretical basis for the prediction, diagnosis, and structural parameter optimization of vertical vibration in large axial Cross-Wedge rolling mill.